The Outcomes of Trabeculectomy following Anti-VEGF Treatments in Neovascular Glaucoma : A Systematic Review and Meta-Analysis: Oral Presentation - Observational Study - General practitioner - Dewi, Ni Putu Ayu Pande Arista (Majalah Oftalmologi Indonesia, 2023)
Introduction Neovascular glaucoma (NVG) is a secondary glaucoma that potentially causes blindness due to proliferation of fibrovascular tissue in the anterior chamber angle. Ischemia in retinal triggers a cascade of various angiogenic factors including vascular endothelial growth factor (VEGF) and interleukin-6 which lead to neovascularization. It was known that anti-VEGF inhibits the primary mediators of neovascularization and control intraocular pressure (IOP) in NVG. Objective To summarize outcome of anti-VEGF with trabeculectomy and applied in clinical practice. Methods PRISMA guideline was followed and analyzed the comparison with Revman (version 5.4). We used databases and professional websites published on eye conditions between 2013-2023 in English. All interventional and observational studies with 95% confidence interval (CI) were used. Risk of bias was measured using funnel plot. Outcomes measured were IOP, Best Corrected Visual Acquity (BCVA), neovascularization iris (NVI) recurrence before and after trabeculectomy. Result Six studies (199 eyes) showed a significant difference in IOP (MD=25.84, 95%CI 24.08-27.60, p< 0.00001) and NVI recurrence (RD=0.94, 95%CI 0.86-1.01, p<0.00001). While four studies (143 eyes) found there was a significant difference in BCVA (MD=0.21, 95%CI 0.06-0.37, p=0.008). The result of NVI should be interpreted with caution and not considered as definitive statement since the data was moderately heterogenic (I2=68% p=0.009). Conclusion It could be concluded there was a significant difference in IOP, BCVA, and NVI recurrence after given anti-VEGF with trabeculectomy. We could not conclude which anti-VEGF gave better result since there were lack of studies, low of studies quality, and heterogen data for NVI recurrence.